Analisis Kecerdasan Intrapersonal Anak Usia Dini di Lembaga PAUD Bintang - Jaya Harjani, Haryanti (ALAYYA : Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to gain a more detailed understanding of intrapersonal intelligence in early childhood at PAUD Bintang Kampung Cadas, Putat Village, Ciseeng District, Bogor Regency, West Java Province. The subjects of this study consisted of 22 children aged 4 to 6 years at PAUD Bintang Kampung Cadas, Putat Village, Ciseeng District, Bogor Regency, West Java Province. This research employs a descriptive qualitative method and uses data analysis techniques by Miles and Huberman. Data collection techniques in this study include observation, interviews, and documentation. Children with intrapersonal intelligence will have a good understanding and control of themselves. Intrapersonal intelligence refers to an individual's ability to understand themselves. This research was conducted from July 2023 to August 2023. The findings of this study highlight the importance of children understanding the actions or behaviors they can and cannot perform in both personal and social environments.